2022
DOI: 10.3389/fmicb.2022.889694
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Microbiota Dysbiosis and Ecological Alterations in Gastric Cancer

Abstract: Changes in bacteriome composition have a strong association with gastric cancer (GC). However, the relationship between stomach fungal microbiota composition and human host immune factors remains largely unknown. With high-throughput internal transcribed spacer region 2 (ITS2) sequencing, we characterized gastric fungal microbiome among the GC (n = 22), matched para-GC (n = 22), and healthy individuals (n = 11). A total of 4.5 million valid tags were generated and stratified into 1,631 operational taxonomic un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…(A) Shay et al (2020) demonstrated the differences of the mycobiome in the oral washings from patients with head and neck squamous cell carcinoma (HNSCC) compared to matched control participants; Mukherjee et al (2017) revealed the differences of the mycobiome in the tumor tissues compared to adjacent non-tumor tissues from patients with oral squamous cell carcinoma OSCC (mobile) in the tongue. (B) Zhong et al (2021) and Zhang et al (2022) revealed the differences of the mycobiome in the tumor tissues compared to adjacent non-tumor tissues from patients with gastric cancer; Yang et al (2022) revealed the differences of the mycobiome in the tumor tissues from patients with gastric cancer compared to normal tissue from healthy controls. (C) Coker et al (2019) and Gao et al (2022) revealed the differences of the mycobiome in the stool samples from patients with colorectal cancer compared to healthy controls.…”
Section: Gut Mycobiota and Gastrointestinal Neoplasmsmentioning
confidence: 99%
See 4 more Smart Citations
“…(A) Shay et al (2020) demonstrated the differences of the mycobiome in the oral washings from patients with head and neck squamous cell carcinoma (HNSCC) compared to matched control participants; Mukherjee et al (2017) revealed the differences of the mycobiome in the tumor tissues compared to adjacent non-tumor tissues from patients with oral squamous cell carcinoma OSCC (mobile) in the tongue. (B) Zhong et al (2021) and Zhang et al (2022) revealed the differences of the mycobiome in the tumor tissues compared to adjacent non-tumor tissues from patients with gastric cancer; Yang et al (2022) revealed the differences of the mycobiome in the tumor tissues from patients with gastric cancer compared to normal tissue from healthy controls. (C) Coker et al (2019) and Gao et al (2022) revealed the differences of the mycobiome in the stool samples from patients with colorectal cancer compared to healthy controls.…”
Section: Gut Mycobiota and Gastrointestinal Neoplasmsmentioning
confidence: 99%
“…Another study was not entirely consistent with these results, as it found no significant difference in alpha and beta diversity between the GC and the matched para-GC groups. However, the results also indicated that compared to gastric tissue from healthy populations, GC tissue had significantly lower alpha diversity of fungi, and the GC group also formed a relatively well-separated fungal flora ( Yang et al, 2022 ). Furthermore, fungal dysbiosis was reflected by a higher proportion of opportunistic fungi, such as Cutaneotrichosporon and Malassezia in patients with GC compared to healthy controls ( Yang et al, 2022 ; Figure 1B ).…”
Section: Gut Mycobiota and Gastrointestinal Neoplasmsmentioning
confidence: 99%
See 3 more Smart Citations